High energy behavior of a six-point R-current correlator in N= 4 supersymmetric Yang-Mills theory - Bartels, Jochen; Ewerz, Carlo (Journal of high energy physics, 2010)
We study the high energy limit of a six-point R-current correlator in N=4N=4 \mathcal{N} = 4 supersymmetric Yang-Mills theory for finite Nc. We make use of the framework of perturbative resummation of large logarithms of the energy. More specifically, we apply the (extended) generalized leading logarithmic approximation. We find that the same conformally invariant two-to-four gluon vertex occurs as in non-supersymmetric Yang-Mills theory. As a new feature we find a direct coupling of the four-gluon t-channel state to the R-current impact factor.
Gesehen am 22.11.2017